MUSIC STREAMING APP: AN INFLUENTIAL LEARNING TOOL TO LEVEL UP STUDENTS’ VOCABULARY - Aminatun, Dyah; Hastomo, Tommy (Jurnal Smart, 2024)
This research aimed to find out if there is a significant effect on students’ vocabulary after using a music streaming application JOOX. It was conducted in the tenth grade of SMA Swadhipa Natar. Using a quasi-experimental study, a test consisting of 30 questions was administered. A t-test was used to analyze the effectiveness of JOOX on students’ vocabulary mastery. The result shows the sig. value (2-tailed) is 0.00 < 0.05. It means that the alternative hypothesis (Ha) is accepted. Therefore, this result concluded that the implementation of JOOX in learning English had a significant effect in boosting students’ vocabulary mastery.